High-resolution Observations of an X-1.0 White-light Flare with Moving Flare Ribbons - Xu Yang; Meiqi Wang; Andrew Cao; Kaifan Ji; Vasyl Yurchyshyn; Jiong Qiu; Sijie Yu; Jinhua Shen; Wenda Cao (The Astrophysical Journal Letters)
We analyze high-resolution observations of an X-1.0 white-light flare, triggered by a filament eruption, on 2022 October 2. The full process of filament formation and subsequent eruption was captured in the H α passband by the Visible Imaging Spectrograph (VIS) on board the Goode Solar Telescope (GST) within its center field of view. White-light emissions appear in flare ribbons following the filament eruption and H α ribbon brightening. GST Broadband Filter Imager data show that the continuum intensity, as compared to the nearby quiet-Sun area, has increased by up to 20% in the photospheric TiO band around 7057 Å. The Helioseismic and Magnetic Imager on board the Solar Dynamics Observatory reported 10% contrast enhancement in the continuum near Fe i 6173 Å line. The separation motion of two white-light kernels is recorded by the high-cadence GST/TiO images and is well accompanied by the motion of the VIS H α flare ribbon leading edge. One kernel, located in a 150 Gauss field within a granulation area, exhibited an average apparent motion speed of 55 km s ^−1 , which is the highest average speed ever reported. The other kernel drifted at 9 km s ^−1 in an 800 Gauss magnetic field area. Hard X-ray (HXR) emissions reaching up to 300 keV have been observed for this flare. The simultaneous occurrence of high-cadence HXR, microwave, and white-light emissions strongly suggests that the energetic particles from the flare directly contribute to the heating. The inverted HXR energy flux density corresponding to 10% TiO brightening is 2.07 ± 0.23 × 10 ^11 erg cm ^−2 s ^−1 during the flare peak.